Improved drug targeting to liver tumor by sorafenib-loaded folate-decorated bovine serum albumin nanoparticles - Haipeng Wang; Shuilin Sun; Yu Zhang; Jiayi Wang; Shouhua Zhang; Xuebing Yao; Ling Chen; Zhen Gao; Baogang Xie (Taylor & Francis Group, 2019)
Background: To prepare sorafenib-loaded folate-decorated bovine serum nanoparticles (FA-SRF-BSANPs) and investigate their effect on the tumor targeting. Methods: The nanoparticles were characterized and evaluated by in vivo and in vitro experiments. Results: SRF-loaded BSA nanoparticles (SRF-BSANPs) was first prepared and modified with folic acid by chemical coupling to obtain FA-SRF-BSANPs. The average particle size, zeta potential, entrapment efficiency, and drug loading of the optimized FA-SRF-BSANPs were 158.00 nm, −16.27 mV, 77.25%, and 7.73%, respectively. The stability test showed that FA-SRF-BSANPs remained stable for more than 1 month at room temperature. The TEM analysis showed that the surface of FA-SRF-BSANPs was nearly spherical. XRD analysis showed that the drug existed in. the nanoparticles in an amorphous state. FA-SRF-BSANPs can promote the intracellular uptake of hepatoma cells (SMMC-7721) with the strongest inhibitory effect compared with SRF-BSANPs and sorafenib solution. Furthermore, the tumor targeting of FA-SRF-BSANPs (Ctumor/Cblood, 0.666 ± 0.053) was significantly higher than those of SRF-BSANPs (Ctumor/Cblood, 0.560 ± 0.083) and sorafenib-solution (Ctumor/Cblood, 0.410 ± 0.038) in nude mice with liver cancer. Conclusion: FA-modified albumin nanoparticles are good carriers for delivering SRF to the tumor tissue, which can improve the therapeutic effect and reduce the side effects of the drug.